(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
Quantitative analysis of planktonic foraminiferal assemblages from Mediterranean Pliocene sections evidenced several fluctuations in abundance which for 4 taxonomic units (Globorotalia inflata group, Globigerinoides ruber, Globigerinoides obliquus and Globigerinoides quadrilobatus) occur cyclically. Estimate of cycle periodicity, using paleomagnetically or biochronologically absolute dated calibration points, proves that abundance fluctuations display a periodicity of about 20 kyr in the lower part of the Pliocene and of about 40 kyr in the upper part of the Pliocene, thus correlatable to the precession and obliquity astronomical cycles respectively. Based on the sequence of abundance fluctuations a precise age estimate was obtained for several biostratigraphic events. Comparison of the ages estimated of the Late Pliocene bio-events between the Mediterranean and North Atlantic regions shows that possible diachroneities occur within a range not greater than 0.1 MA. A more detailed biostratigraphic scheme for the planktonic foraminifera, including four new subzones, is proposed for the Mediterranean area.